2018
DOI: 10.14740/cr795
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Novel Long-Tapered Sirolimus-Eluting Coronary Stent System in Real-World Patients With Long Diffused De Novo Coronary Lesions

Abstract: BackgroundWhen coronary lesions involve segments > 48 mm, the only treatment possibility is stent overlapping which is associated with higher neointimal proliferation that lead to more restenosis. Furthermore, tapering of coronary arteries is a major challenge observed with long diffuse coronary lesions. This study attempted to assess the safety and performance of world’s first commercialised long-tapered (60 mm) sirolimus-eluting coronary stent (SES) system for the treatment of long diffused de novo coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The BioMime Morph is a biodegradable polymer-based sirolimus-eluting novel tapered stent with the ultra-thin strut of 65 m of cobalt chromium platform. Studies have shown that the usage of tapered stents in daily clinical practice showed good apposition and coronary flow without any complications [ 6 , 7 ]. Very few cases documented the feasibility of using long-tapered stents in diseases involving the left main [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BioMime Morph is a biodegradable polymer-based sirolimus-eluting novel tapered stent with the ultra-thin strut of 65 m of cobalt chromium platform. Studies have shown that the usage of tapered stents in daily clinical practice showed good apposition and coronary flow without any complications [ 6 , 7 ]. Very few cases documented the feasibility of using long-tapered stents in diseases involving the left main [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the usage of tapered stents in daily clinical practice showed good apposition and coronary flow without any complications [ 6 , 7 ]. Very few cases documented the feasibility of using long-tapered stents in diseases involving the left main [ 6 ]. Here, we report the case of complex triple vessel disease with left main involvement and CTO of RCA which was managed successfully with long-tapered BioMime Morph stents.…”
Section: Discussionmentioning
confidence: 99%
“…Current strategies to treat TCALs include overlapped stenting with multiple short stents [26][27][28], single stenting with a conventional long tubular stent [29,30], or single stenting with a tapered long stent [18][19][20][21][22][23].…”
Section: Controversial Outcomes Of Current Stenting Strategies For Tcalsmentioning
confidence: 99%
“…To overcome this dilemma, conventional overlapped stenting (COS) offers an option but may increase risks of in-stent restenosis or thrombosis, as well as the therapeutic cost [11][12][13][14][15][16][17]. Recently, a long tapered stent customized for TCALs has been developed but is not yet extensively used [18][19][20][21][22][23]. Accordingly, we proposed a modified single stenting (MSS) by using a conventional long stent for TCAL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially useful for long lesions where the use of tapered single coronary stent may provide better vessel adaptation and superior long-term outcomes apart from curtailing the financial cost. A few studies evaluating the efficacy of this novel concept have found encouraging results (6,7), In this study, we aimed to study the peri-procedural safety, and one-year outcomes of patients undergoing treatment with the BioMime Morph SES in the high-risk Indian population.…”
Section: Introductionmentioning
confidence: 99%